Inferring the potential impact of human activities on evapotranspiration in the Tumen River Basin based on LANDSAT imagery and historical statistics. (6th October 2020) - Yu, Hangnan; Lee, Woo‐Kyun; Li, Lan; Jin, Ri; Zhu, Weihong; Xu, Zhen; Cui, Guishan
Abstract: Understanding the spatial and temporal changes in actual evapotranspiration (ETa ) caused by different human activities is important for water management in water‐sensitive areas, because ETa plays a major role in regulating the availability of water on land. Thus, ETa observation is particularly important for observing land degradation in the watershed. This study used the operational simplified surface energy balance (SSEBop) model to perform ETa estimations and observations in the Tumen River Basin (TRB), covering the border of China and Democratic People's Republic of Korea (DPRK), over the last 30 years by using eight periods of clear‐sky LANDSAT Thematic Mapper/Operational Land Imager (TM/OLI) and thermal infrared sensor (TIRS) data. To assess the reliability of the ETa estimations, multilayer soil temperatures from the China Meteorological Administration (CMA) Land Data Assimilation System Version 2.0 (CLDAS‐V2.0) were utilized. The highest R 2 (.71) between ETa and soil temperature was observed in layers shallower than 10 cm; this value of R 2 gradually decreased to .57 at a depth of 200 cm. The average ETa of the TRB declined from 1.65 mm in 1985 to 1.03 mm in 2017. The impact of human activities on water loss (ETa ) was determined by comparing land cover changes observed by an object‐based image analysis (OBIA) approach and economic activities between 1994 and 2008. Varying economic activities and water depletion in different soil layers may have led to the variable ETa values between the northern (China) and southern (DPRK) part of the TRB during the last three decades.